Factors that Cause Mental Health Problems in Covid-19 Nurses - Riza Arisanty Latifah; Rully Annisa (UM Purwokerto Press, 2021)
Covid-19 is an infectious disease that is endemic in all countries in the world, including Indonesia. Nurses who are frontline health workers are significantly at risk of experiencing Covid-19 transmission. This causes several mental health problems such as anxiety, stress, insomnia, excessive fear and even depression. So researchers need to study further what factors can cause mental health problems in COVID-19 nurses. This research is quantitative research with a correlation approach. This research was conducted at Gunung Jati Hospital, Cirebon. The sample in the study amounted to 60 nurses. The sampling technique was purposive sampling, with inclusion and exclusion criteria determined by the researcher. Data collection techniques through google forms using the Self Reporting Questionnaire (SRQ). The statistical test used is the Chi-Square Test using SPSS. The results of this study indicate that there is a relationship between age (p=0.000); Gender (p= 0.003), marital status (p=0.002), on mental health problems for Covid-19 nurses. There is a relationship between age, gender, gender and marital status, with the mental health of COVID-19 nurses.